Fraturas do arco zigomático: cerclagem de contenção - Nelson Ribeiro Neto (2006)
This work proposes an alternative technique for zygomatic fractures contention. Steel wire cerclage supports an 1.5 Kirchner wire shaped in double U by cutaneous anchorage. This technique can be indicated in cases of closed reduction of zigomatic arch fractures without fixation that may loose reduction if not properly protected.